Comparative Evaluation of Chromatographic Techniques for Radiochemical Control of 99mTc-MIBI (MIBI = 2-Methoxy-2-isobutyl isonitrile) - Daci, Brunilda; Bylyku, Elida; Malja, Skender (Asian Journal of Chemistry, 2010)
Quality control of radiopharmaceuticals is important, providing products of high standards. The current study refers to comparative evaluation of chromatographic techniques applied to the MIBI (2-methoxy-2-isobutyl isonitrile) after labeling with 99mTc. Three chromatographic techniques are performed and evaluated taking into account different parameters such as true separation, shape of the chromatographic peaks, time required, ease of handling, cost, etc. The scoring system is established according to the relative importance of each factor considered. The results indicated that instant thin layer chromatography is the best quality control method for radiochemical evaluation of 99mTc-MIBI with application in nuclear medicine. It would appear that PC Whatman 4 and 1Chr can use with success and can replace instant thin layer chromatography method, because of its cost.